Using EPIC to Find Conflicts, Inconsistencies, and Gaps in Department of Defense Policies - Wong, Carolyn (RAND Corporation, 2013)
The authors present a framework and methodology to identify the roles and responsibilities of those implementing Department of Defense policies and also potential conflicts, ambiguities, gaps, inconsistencies, and redundancies in those policies. They introduce a new software tool that automates one step of the methodology-EPIC-and demonstrate its use with three case studies to illustrate the technique and also the tool's flexibility.